Associations of specific phobia and its subtypes with physical diseases: an adult community study. Issue 1 (December 2016) - Witthauer, Cornelia; Ajdacic-Gross, Vladeta; Meyer, Andrea; Vollenweider, Peter; Waeber, Gerard; Preisig, Martin; Lieb, Roselind
Abstract Background Specific phobia is the most prevalent anxiety disorder in the community and is associated with substantial impairment. Comorbidity with physical diseases is assumed and has important implications for etiology, treatment, or prevention of the comorbid conditions. However, due to methodological issues data are limited and subtypes of specific phobia have not been investigated yet. We examined the association of specific phobia and its subtypes with physical diseases in a representative community sample with physician-diagnosed physical diseases and diagnostic criteria of specific phobia. Methods Data of the German Mental Health Survey from 4181 subjects aged 18–65 years were used. Specific phobia was diagnosed using M-CIDI/DIA-X interview; physical diseases were assessed through a self-report questionnaire and a medical interview. Logistic regression analyses adjusted for sex were calculated. Results Specific phobia was associated with cardiac diseases, gastrointestinal diseases, respiratory diseases, arthritic conditions, migraine, and thyroid diseases (odds ratios between 1.49 and 2.53). Among the subtypes, different patterns of associations with physical diseases were established. The findings were partially replicated in the Swiss PsyCoLaus Study. Conclusions Our analyses show that subjects with specific phobia have an increased probability for specific physical diseases. From these analyses etiological mechanisms of specific phobia and physical disease can be deduced. As subtypes differed in their patterns of associations with physical diseases, different etiological mechanisms may play a role. The findings are highly relevant for public health in terms of prevention and therapy of the comorbid conditions.